Medicinal plants used as abortifacients by the Scheduled Caste community of Manipur, India - Phurailatpam, Anjali Devi; Nongmaithem, Rita; Devi, Leishangthem Ranibala; Devi, Sanjenbam Sanjibia; Devi, Thokchom Tamphamani (Journal of Medicinal Herbs and Ethnomedicine, 2025)
An ethnobotanical study was conducted to document the traditional knowledge of medicinal plants used as abortifacients by the Lois, a Scheduled Caste community residing in Phayeng, Khurkhul, Andro, Thanga and Kakching areas of Manipur. Information about these plants was gathered through personal interviews using a semi-structured questionnaire with elderly individuals from the selected study areas. The study identified eighteen (18) plant species from fourteen (14) different families that are utilized by the Lois people as abortifacients. Leaves were the most frequently used plant parts, while latex was found to be the least used plant part. Quantitative ethnobotanical indices, such as the Disease Consensus Index (DCI) were calculated to determine the level of agreement among informants regarding the uses of these plants for abortion. Furthermore, Preference Ranking was carried out for the eight selected species with high DCI value to assess their relative importance and effectiveness among the five study sites. Urbanization and modernization have led to a decline in traditional knowledge regarding plants used as medicine and many valuable plants are now at risk. It is crucial to preserve such ethnobotanical knowledge before this valuable traditional wisdom is lost forever.